Post-total abdominal hysterectomy pain experience of patients at academic hospitals with and without a pain service - Malumalu, Utshudi Joe (My University, 2022)
Background Acute post-operative pain management remains sub-optimal despite introducing acute pain services. Not all hospitals have an acute pain service, and where they do exist, there is wide variability in efficiency. This study aimed to compare the pain experience on Day 1 post-total abdominal hysterectomy (TAH) of patients exposed to a pain service at Rahima Moosa Mother and Child Hospital (RMMCH) and those at Chris Hani Baragwanath Academic Hospital (CHBAH) with no pain service. Methods A comparative cross-sectional research design was followed using convenience sampling. The PAIN-OUT questionnaire was used to collect data. There were 72 patients from RMMCH and 70 from CHBAH enrolled in the study. Results There were no significant differences between the worst and least pain scores and time in severe pain between the patients at RMMCH and CHBAH with median scores of 7 versus 8 (p=0.6490), 3 versus 4 (p=0.064) and 40% versus 45% (p=0.195), respectively. There were also no significant differences in pain scores for in-bed activities 4 versus 5 (p=0.166) or the incidence of nausea, drowsiness, itching and dizziness 0 versus 1 (p=0.089), 3 versus 3 (p=0.498), 0 versus 0 (p=0.441) and 2 versus 2 (p=0.626), respectively. Satisfaction with pain management was not significantly different between the patients at the two hospitals, 9 versus 8 (p=0.123). Conclusion Although post-operative pain management is regarded as a fundamental human right, TAH post-operative pain was poorly managed in this study. There was no significant difference between the pain scores and the side effects experienced between patients at the two hospitals, despite an office-hours acute pain service at one of the hospitals. Patients at RMMCH experienced significantly less pain with out of bed activities, deep breathing or coughing and sleeping and felt less anxious and helpless. Patients at both hospitals were satisfied with pain management.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Medicine in Anaesthesiology to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, 2022